Analysis of oligomers in poly (butylene succinate) and poly (butylene adipate-co-terephthalate) - Zhang, Chuanhui; Chen, Chao; Ouyang, Chunping; Zeng, Xiangbin; Guo, Zhilong; Lai, Fenghua; Li, Jianjun (Polymer bulletin (Berlin, Germany), 2023)
Aliphatic and aliphatic–aromatic polyesters are used widely in the food packaging field, which is very concerned about the volatile organic compound (VOC). Typical VOCs in poly (butylene succinate) (PBS) and poly (butylene adipate-co-terephthalate) (PBAT) are oligomers, especially cyclic esters, which were studied using GPC, MALDI-FTICR-MS and UPLC-FTICR-MS technique. Cyclic esters with repeating unit 2–8 were found in PBS; cyclic esters with repeating unit 1–10 (or more) were found in PBAT derived from three monomers with almost all possible random combinations. Cyclic esters with repeating unit 2–4 were the most abundant structures, but only cyclic esters with repeating unit 1–3 were found in the crystalline extracted from the recovered butanediol from the product line. Cyclic esters with repeating unit 1–3 can also be extracted from methanol at 70 °C for 1 h, and the content of linear oligomers increased with increasing temperature to 200 °C. But PBAT resin cannot be decomposed to monomers at 200 °C for 1 h in methanol without other additives. Graphical abstract